2023
DOI: 10.1057/s41599-023-02380-9
|View full text |Cite
|
Sign up to set email alerts
|

Gendered vulnerabilities to climate change and farmers’ adaptation responses in Kwara and Nassarawa States, Nigeria

Ayansina Ayanlade,
Isaac A. Oluwatimilehin,
Oluwatoyin S. Ayanlade
et al.

Abstract: This study examines gender vulnerabilities and responsive strategies to climate change, comparing evidences from Kwara and Nassarawa States in Nigeria. Changes in climate parameters, gender-based perceptions of climate, as well as gender-based response and adaptation practices were assessed in accordance with specific research objectives. A total of 200 participants were surveyed through a mixed method approach using 41 years of climate data. Semi-structured questionnaires were administered equally in the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…The average household size in the area was 7 persons, suggesting that the arable crop farmers had quite high households, some of which may have included direct family, relatives, or extended dependents who could help with farming production and practice more climate change adaptation strategies in the area. The result was in consonance with the study of Ayanlade et al [14], who found that "household size could be a proxy for labour to increase and enhance their farming activities, climate change adaptation and expansion of farm income". The average length of time spent in school was 12 years, which suggests that the arable crop farmers in the region had at least a secondary education.…”
Section: Socio-economic Characteristics Of Arable Crop Farmerssupporting
confidence: 90%
“…The average household size in the area was 7 persons, suggesting that the arable crop farmers had quite high households, some of which may have included direct family, relatives, or extended dependents who could help with farming production and practice more climate change adaptation strategies in the area. The result was in consonance with the study of Ayanlade et al [14], who found that "household size could be a proxy for labour to increase and enhance their farming activities, climate change adaptation and expansion of farm income". The average length of time spent in school was 12 years, which suggests that the arable crop farmers in the region had at least a secondary education.…”
Section: Socio-economic Characteristics Of Arable Crop Farmerssupporting
confidence: 90%
“…Better access to market information can be ensured by enhanced social capital and information-sharing platforms [10,43]. For instance, women with less access to resources, such as information, credit, and market services, are less likely to adopt climate change adaptation strategies, increasing vulnerability to climate risks [17,18]. Therefore, the scores for this component highlight the need for more concerted action and emergency COVID-19 responses from public and private organisations to meet the needs of vulnerable farm households in the coastal areas of Myanmar and Vietnam.…”
Section: Social-network Componentmentioning
confidence: 99%
“…The effects of climate change are not evenly distributed, and marginalised groups, including women, are disproportionately affected. Female farmers frequently face genderspecific barriers to resources and decision-making power, exacerbating their vulnerability to climate risks [16,17]. In many regions, women play an important role in food production, processing, and marketing, and their vulnerability has consequences for agricultural productivity and food security.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation